Q: 3x² - 17x +10 = 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Do you mean: 3x2-17x+10? If so then it is: (3x-2)(x-5)

That factors to (x + 5)(3x + 2)

17x - 8 = 3x + 16 Add 8 to each side: 17x = 3x + 24 Subtract 3x from each side: 14x = 24 ie 7x = 12 so x = One and five-sevenths

-6x2 + 17x -12. To get the solution, we set up the formula as follows: (2x - 3) * (4 - 3x) Then we multiply each of the components as follows: (2x * 4) + (2x * -3x) + (-3 * 4) + (-3 * -3x) Then we simplify as follows: 8x + -6x2 + -12 + 9x -6x2 + 17x + -12 -6x2 + 17x -12

5*2-3x-1 = 0 10-3x-1 = 0 -3x = 1-10 -3x = -9 x = 3

Related questions

Do you mean: 3x2-17x+10? If so then it is: (3x-2)(x-5)

3x+y=5(4x-7y)=-10 3x+y=20x-35y=-10 -3x -3x y=17x-35y=-10 -y -y 17x-36y=-10 sorry but that's as far as i could get :(

(3x + 2)(x + 5)

That factors to (x + 5)(3x + 2)

If you mean 3x - 2x * 3x * 43x - 2x * 3x * 43x - 5x * 43x - 20x-17x (negative 17x) is your answer

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

17x - 8 = 3x + 16 Add 8 to each side: 17x = 3x + 24 Subtract 3x from each side: 14x = 24 ie 7x = 12 so x = One and five-sevenths

6x2-17x+7 = (2x-1)(3x-7) when factored

-6x2 + 17x -12. To get the solution, we set up the formula as follows: (2x - 3) * (4 - 3x) Then we multiply each of the components as follows: (2x * 4) + (2x * -3x) + (-3 * 4) + (-3 * -3x) Then we simplify as follows: 8x + -6x2 + -12 + 9x -6x2 + 17x + -12 -6x2 + 17x -12

5*2-3x-1 = 0 10-3x-1 = 0 -3x = 1-10 -3x = -9 x = 3

If this question is: (17)(-83)(16), then the answer is -22,576.

(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out